2022
DOI: 10.3389/fimmu.2022.879775
|View full text |Cite
|
Sign up to set email alerts
|

Arabinogalactan enhances Mycobacterium marinum virulence by suppressing host innate immune responses

Abstract: Arabinogalactan (AG) participates in forming the cell wall core of mycobacteria, a structure known as the mAGP complex. Few studies have reported the virulence of inartificial AG or its interaction with the host immune system. Using clustered regularly interspaced short palindromic repeats interference gene editing technology, conditional Mycobacterium marinum mutants were constructed with a low expression of embA or glfT2 (EmbA_KD or GlfT2_KD), which are separately involved in the biosynthesis of AG arabinose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…In our study, we found that supplementation with SA has no effects on the growth of Mm , while noticeably inhibiting Mm invasion into the lung epithelial cells. This lack of effect on Mm growth may be attributed to the arabinogalactan-containing cell wall of Mm , which serves as a natural barrier between Mycobacterium and antibiotics [ 45 ]. Next, a series of experiments in our study demonstrated that SA suppresses the production of proinflammatory cytokines and inhibits the expression of iNOS and COX-2 in macrophages after Mm infection, parallel to the protective role of SA in isoproterenol-induced cardiotoxicity rats [ 29 ], suggesting it has potential anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that supplementation with SA has no effects on the growth of Mm , while noticeably inhibiting Mm invasion into the lung epithelial cells. This lack of effect on Mm growth may be attributed to the arabinogalactan-containing cell wall of Mm , which serves as a natural barrier between Mycobacterium and antibiotics [ 45 ]. Next, a series of experiments in our study demonstrated that SA suppresses the production of proinflammatory cytokines and inhibits the expression of iNOS and COX-2 in macrophages after Mm infection, parallel to the protective role of SA in isoproterenol-induced cardiotoxicity rats [ 29 ], suggesting it has potential anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis, a widespread global infectious disease, is caused by Mycobacterium tuberculosis [ 1 ]. Spinal tuberculosis (STB) accounts for about 2% of all tuberculosis cases, about 15% of extra-pulmonary tuberculosis, and 50% of all bone tuberculosis, making it the most common form of bone and joint tuberculosis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%